1994
DOI: 10.1073/pnas.91.18.8646
|View full text |Cite
|
Sign up to set email alerts
|

Autoantigenic proteins that bind recombinogenic sequences in Epstein-Barr virus and cellular DNA.

Abstract: We have identified conserved autoantigenic cellular proteins that bind to G-rich sequence motifs in recombinogenic regions of Epstein-Barr virus (EBV) DNA. This binding activity, called TRBP, recognizes the EBV terminal repeats, a locus responsible for interconversion of linear and circular EBV DNA. We found that TRBP also binds to EBV DNA sequences involved in deletion of EBNA2, a gene product required for immoralization. We show that TRBP binds sequences present in repetitive cellular DNA, such as variablenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…A highly conserved cellular protein has been found to bind to the termini of EBV in vitro, and its binding site spans the 11-bp element. It has been suggested that the protein is involved in such recombination processes, which remains to be demonstrated (21).…”
Section: Discussionmentioning
confidence: 99%
“…A highly conserved cellular protein has been found to bind to the termini of EBV in vitro, and its binding site spans the 11-bp element. It has been suggested that the protein is involved in such recombination processes, which remains to be demonstrated (21).…”
Section: Discussionmentioning
confidence: 99%
“…Failure of EBV to circularize in T cells thus appears to indicate a critical block in the progression of EBV infection to the latent program of gene expression readily demonstrated in B cells (Alfieri et al 1991). To our knowledge, there is no current description of the mechanism which EBV and other herpes viruses utilize to form the viral episome from the linear infectious form during the establisbment of latency, although some evidence suggests that EBV uses a pathway similar to the immunoglobulin class switcbing pathway for the transition from the circular to the linear form during viral reactivation (Sun et al 1994).…”
Section: Importance Of the Linear To Circular Genome Transition In Ebmentioning
confidence: 99%
“…The DBP may also have a role in the reverse transition of the circular genome to the linear state during lytic induction of the virus (Decaussin et al 1995). Since some indirect evidence suggests that the linearization of EBV from the circular episomal form utilizes sequences similar to the sequences recognized during class switch immunoglobulin recombination (Sun et al 1994), cleavage at class switch sequences may also be a DBP function. Hence, both immunoglobulin V(D)J recombination and immunoglobulin class switching recombination may simultaneously have arisen via integration and duplication of portions of an extrachromosomal element, a coincidence previously only suspected for the origins of V(D)J recombination (reviewed in Dreyfus 1992, Thompson 1995.…”
Section: Modulation Of Cellular Rag Expression Via Ebv Infection Of Bmentioning
confidence: 99%
“…In the infected cell, EBV is maintained extrachromosomally in a circular (latent) or linear (replicating) molecular configuration (1,12,29). Recent detection in human lesions of EBV DNA rearrangement (31,39,43) and chromosomal integration (20,35) suggests that recombination events are a central feature of EBV biology and pathogenesis (41,46). Because internal rearrangements in the viral genome exhibit general sequence specificity (9,16,31,41), we questioned whether site-specific recombinases involved in diversification of the host immune response mediate DNA rearrangements in this lymphotropic virus.…”
Section: In Experimental B-cell Infections Epstein-barr Virus Inducementioning
confidence: 99%
“…Although insufficient to implicate V(D)J recombinase specifically, viral integration does indicate the presence of recombinogenic activity in RAG-positive cells. Whether increased RAG transcription correlates with a functional V(D)J recombinase or represents a more general stimulation of cellular recombination mechanisms (3,41) is the focus of ongoing studies.…”
Section: In Experimental B-cell Infections Epstein-barr Virus Inducementioning
confidence: 99%